Three cases of colon cancer in four generations of the Saudi family, caused by endogamous germline mutations: colon cancer caused by Germline Mutations - Alshaya, Dalal S.; Al-Hazani, Tahani Mohamed Ibrahim; Alotaibi, Mashael Alhumaidi; Domiaty, Dalia Mostafa; Alshehri, Eman; Abdulla Alwaili, Maha; Alotaibi, Amani Mohammed; Jalal, Areej Saud; AlQahtani, Alaa Ali; AlQassim, Fatima Abdullah; Albasher, Gadah; Saeed Al-Qahtani, Wedad (Cellular and Molecular Biology, 2023)
Various research pieces of evidence have been published in recent years, establishing the increasing prevalence of early colon cancer among young people. In this background, the current study aimed to analyze the reasons behind colon cancer recurrence among endogamous consanguineous cases in four generations of a single Saud family. For this study, the authors conducted the whole-exome sequencing analysis to screen for germline mutations in DNA samples from consanguineous cases within the family. After collecting the colon samples, it was analyzed histologically and immunohistochemically with the help of Breast Cancer antibodies (BRCA2 and 1 correspondingly) and H&M staining (hematoxylin and eosin). For this study, 26 at-risk consanguineous cases were considered. Three cases were diagnosed with malignant colon cancer, two with breast cancer, and 17 with germline mutations, yet remain unaffected by cancerous tumors. The rest, four consanguineous cases, are healthy and non-carriers of the mutations. However, as per the exome analysis outcomes, 15 cases inherited germline mutations in nine genes. Nine substitution mutations were present in six of the nine inherited genes in these inherited germline mutations. Furthermore, it also presented six insertion and deletion frameshift mutations in five of nine inherited genes. The immunohistochemical staining process achieved positive staining outcomes for BRCA1 and 2. Therefore, germline mutations inherited from the nine genes of endogamous consanguineous cases of mutation carriers remain the primary reason behind colon cancer recurrence in the same family.